Code-Switching Patterns of Senior High School Students and Teachers in the Technical Vocational and Livelihood (TVL) Shops And Language Classes: Basis for Intervention - Michelle U. Bayucan; Romel R. Costales (Randwick International of Education and Linguistics Science Journal, 2023)
This study looked into the code-switching patterns of the students and teachers of Isabela School of Arts and Trades Senior High School in the Technical Vocational and Livelihood (TVL) shops and language classes as a basis for intervention in classroom instruction. The study used the descriptive research design. Respondents of the study were five teachers of Technical Drafting, Bartending, Bread and Pastry Production (BPP) and Oral Communication and 105 students in the City Division of Ilagan during the School Year 2019-2020. The instruments used were questionnaire and unstructured interview. Based on the findings of the study, code switching is prevalent in classroom instruction and the most commonly used type is intrasentential. Students’ use of code switching is due to many reasons foremost of which is difficulty driven. This means that they lack the ease to transmit messages in the target language thus they code switch. Secondly, they code switch in consideration of the various linguistic backgrounds of the interlocutors as well as to promote solidarity with them. Lastly, they resort to code switching when they put emphasis more on the meaning or communicative intentions and stress out a point over the language itself. Sex does not influence the type of students’ code switching but it is affected by their age, language spoken and specialization.